Determinants of cognitive outcomes of perinatal and childhood stroke: A review. Issue 1 (2nd January 2016) - Fuentes, Amanda; Deotto, Angela; Desrocher, Mary; deVeber, Gabrielle; Westmacott, Robyn
Abstract : Our understanding of cognitive and behavioral outcomes of perinatal and childhood stroke is rapidly evolving. A current understanding of cognitive outcomes following pediatric stroke can inform prognosis and direct interventions and our understanding of plasticity in the developing brain. However, our understanding of these outcomes has been hampered by the notable heterogeneity that exists amongst the pediatric stroke population, as the influences of various demographic, cognitive, neurological, etiological, and psychosocial variables preclude broad generalizations about outcomes in any one cognitive domain. We therefore aimed to conduct a detailed overview of the published literature regarding the effects of age at stroke, time since stroke, sex, etiology, lesion characteristics (i.e., location, laterality, volume), neurologic impairment, and seizures on cognitive outcomes following pediatric stroke. A key theme arising from this review is the importance of interactive effects among variables on cognitive outcomes following pediatric stroke. Interactions particularly of note include the following: (a) age at Stroke x Lesion Location; (b) Lesion Characteristics (i.e., volume, location) x Neurologic Impairment; (c) Lesion Volume x Time Since Stroke; (d) Sex x Lesion Laterality; and (e) Seizures x Time Since Stroke. Further, it appears that these relationships do not always apply uniformly across cognitive domains but, rather, are contingent upon the cognitive ability in question. Implications for future research directions are discussed.